(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Alzheimer’s disease (AD) likely results from a variety of circumstances, which makes understanding the molecular mechanisms behind the neuropathology of the illness challenging. Consequently, it is not unexpected that a variety of potential therapy modalities addressing various features of this condition are now being researched. They include methods to stop the accumulation of amyloid, stop neuronal deterioration, and raise levels of brain neurotransmitters. Here, we go through potential roles for endogenous inhibitors of amyloid aggregation in AD as well as a few of the approaches being considered right now to affect the quantities of amyloid in the brain, its aggregation, and its neurotoxicity. In the future, a viable strategy for the prevention and treatment of AD may consist of stimulating the body’s natural system for peptide clearance and inhibiting amyloid aggregation. There is an urgent need for novel therapeutics for Alzheimer’s disease (AD). Phase I, phase II, and phase III are the stages of the drug development process. On the federal government’s database, trials are listed.